Using qualitative research methods to understand how surgical procedures and devices are introduced into NHS hospitals: the Lotus study protocol - Jane M Blazeby; Natalie S Blencowe; Anni Skilton; Jenny Donovan; Kerry Avery; Sian Cousins; Daisy Elliott; Hollie Richards; Jesmond Zahra; Sangeetha Paramasivan; Johnny Mathews; Barry Main; et al. (BMJ Open)
Introduction The development of innovative invasive procedures and devices are essential to improving outcomes in healthcare. However, how these are introduced into practice has not been studied in detail. The Lotus study will follow a wide range of ‘case studies’ of new procedures and/or devices being introduced into NHS trusts to explore what information is communicated to patients, how procedures are modified over time and how outcomes are selected and reported.Methods and analysis This qualitative study will use ethnographic approaches to investigate how new invasive procedures and/or devices are introduced. Consultations in which the innovation is discussed will be audio-recorded to understand information provision practice. To understand if and how procedures evolve, they will be video recorded and non-participant observations will be conducted. Post-operative interviews will be conducted with the innovating team and patients who are eligible for the intervention. Audio-recordings will be audio-recorded, transcribed verbatim and analysed thematically using constant comparison techniques. Video-recordings will be reviewed to deconstruct procedures into key components and document how the procedure evolves. Comparisons will be made between the different data sources.Ethics and dissemination The study protocol has Health Research Authority (HRA) and Health and Care Research Wales approval (Ref 18/SW/0277). Results will be disseminated at appropriate conferences and will be published in peer-reviewed journals. The findings of this study will provide a better understanding of how innovative invasive procedures and/or devices are introduced into practice.